Pendampingan Membaca Al-Qur'an Melalui Penerapan Metode Tartil Dan Ummi Pada Santri TPQ Nurul Iman - Jumanah Jumanah; M. Taufiqurrahman; Nanda Damara; Rensi Amalia; Siti Wahyuni; Vionika Febrianti (CV. ITTC INDONESIA, 2026)
The ability to read the Qur'an is a fundamental skill that should be developed from an early age. However, several students at TPQ Nurul Iman still experience difficulties in reading the Qur'an accurately and fluently. This community service activity focused on mentoring Qur'anic reading through the implementation of the Tartil and Ummi methods. The mentoring program was conducted through both group-based and individual sessions tailored to the students' reading proficiency levels. The implementation of these methods supported a more structured mentoring process and assisted students in improving their pronunciation of Arabic letters (makharijul huruf) and application of tajwid rules. The results showed that the mentoring activities contributed to better reading habits and provided direct guidance for students in reading the Qur'an according to proper recitation rules. The Tartil and Ummi methods can be utilized as mentoring approaches to support Qur'anic reading development in nonformal Islamic educational institutions.